PENGEMBANGAN MODUL EDUKASI UNTUK MENGURANGI PERILAKU BULLYING PADA SISWA SEKOLAH MENENGAH ATAS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop an educational module to reduce bullying behavior towards students of SMA Negeri 12 Pekanbaru. The research method used is research development (Research and Development) concerning the flow of R&D level 1 steps, namely: Potentials and problems, information gathering and literature studies, product design, design validation, and tested design. The instrument used was the assessment scale sheet, which was validated by 4 material experts, two BK lecturers, and two BK teachers. The results showed that the education module to reduce bullying behavior developed in the usability aspect was included in the Useful category, for the feasibility aspect it was in the Appropriate category, and for the accuracy aspect it was in the Right category.Keywords: Education Module, Bullying Behavior